Restricting spatial lives? The gendered implications of conservation in Cambodia's protected wetlands. (March 2019) - Perry, Nicola; Gillespie, Josephine
Environmental conservation through the creation of protected areas is recognised as a key tactic in the fight against degrading ecosystems worldwide. Understanding the implications of protected area regimes on both places and people is an important part of the protection agenda. In this context and in this paper, we build on the work of feminist legal geographers and feminist political ecologists to enhance our understanding of the constitution of localised socio-legal-environmental interactions in and around protected areas. Our approach looks to developments in feminist and legal geographic thought to examine the interactions between identities, law and the environment in a Ramsar protected wetland on the Tonle Sap, Cambodia. We bring together legal geography perspectives regarding the spatiality of law with insights from feminist political ecology examining gendered roles and exclusions. We found that conservation areas interact in complex ways with local pre-existing norms prescribing female weakness and vulnerability which, ultimately, restrict women's spatial lives.